A cognitive approach to L2 reading comprehension and the limits of description - Gómez, Juan David (Colombian Applied Linguistics Journal, 2016)
This article sets out to assess the impact of the descriptive trend in the field of cognitive and metacognitive strategies and L2 reading comprehension. It does so with the intention of determining what the descriptive trend has contributed and what aspects of the field remain underserved. This assessment is carried out by tracing the roots of cognitive approaches in this field, identifying the components of descriptive research, and looking at representative samples and their contributions. The results of this analysis show that the kind of descriptive research that is most prevalent in the field has perhaps reached a saturation point, that it now offers only limited utility to teachers of reading comprehension, and that some excesses in the field may in fact be detrimental to the population that it looks to serve. The possible impact of these findings and suggestions for alternative avenues of future research that can complement the advances that have been made are discussed.